2017
DOI: 10.1002/lary.27004
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic analysis of spontaneous recurrent laryngeal nerve reinnervation in a rat model

Abstract: NA. Laryngoscope, 128:E117-E122, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Iatrogenic recurrent laryngeal nerve (RLN) injury is a common complication of anterior neck surgical procedures, such as cervical spinal surgery or thyroidectomy . Injury to the RLN results in ipsilateral vocal fold (VF) paralysis that may contribute to dysphagia, dysphonia, and/or dyspnea (i.e., swallow, voice, and respiratory dysfunction, respectively) . These conditions are devastating for patients, especially if chronically persistent, as they are associated with poor quality of life, major depression, increased financial burden, and decreased general health .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iatrogenic recurrent laryngeal nerve (RLN) injury is a common complication of anterior neck surgical procedures, such as cervical spinal surgery or thyroidectomy . Injury to the RLN results in ipsilateral vocal fold (VF) paralysis that may contribute to dysphagia, dysphonia, and/or dyspnea (i.e., swallow, voice, and respiratory dysfunction, respectively) . These conditions are devastating for patients, especially if chronically persistent, as they are associated with poor quality of life, major depression, increased financial burden, and decreased general health .…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are devastating for patients, especially if chronically persistent, as they are associated with poor quality of life, major depression, increased financial burden, and decreased general health . Furthermore, effective treatment options to promote RLN regeneration and restore full functionality of the injured VF are lacking …”
Section: Introductionmentioning
confidence: 99%
“…Unilateral injured RLN shows a robust capacity for regeneration; axons sprout from the proximal stump to seek open endoneurial tubules as new pathways through which to reach the laryngeal musculature as early as 1 week after injury. 20 Our previous study showed that spontaneous RLN regeneration is involved in reinnervation of the laryngeal muscles following laryngeal denervation. 21 Functional recovery of the affected vocal fold depends on reinnervation and synkinesis.…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐sections of 14 μm were obtained. Muscle sections were processed with acetylcholinesterase (motor endplates), α‐bungarotoxin (acetylcholine receptors), and a neurofilament antibody (nerve fibers) as described in our previously published protocol 14 . Images were taken at 40× magnification using a Nikon A1 confocal microscope (Nikon, Tokyo, Japan); the microscopic images were converted to digital images for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-sections of 14 μm were obtained, and the sections were stained with a neurofilament antibody as previously described. 14 Fluorescent microscopy at 20× magnification was performed via a Nikon Microphot FXA fluorescent microscope (Nikon). The microscopic images were converted to digital images for quantification.…”
Section: Nerve Histomorphometric Analysismentioning
confidence: 99%